The impact of tree crops and temperature on the timing of frugivorous bird migration - Kanerva Anna-Maria; Hokkanen Tatu; Lehikoinen Aleksi; Norrdahl Kai; Suhonen Jukka (SPRINGER, 2022)
Migration has evolved to tackle temporal changes in availability of resources. Climate change has been shown to affect the migration dates of species, which raises the question of whether the variation in the timing of migration is climate or resource dependent? The relative importance of temperature and availability of food as drivers of migration behaviour during both spring and autumn seasons has been poorly studied. Here, we investigated these patterns in frugivorous and granivorous birds (hereafter frugivorous) that are assumed to postpone their autumn migration when there is plenty of food available, which may also advance upcoming spring migration. On the other hand, especially spring migration dates have been negatively connected with increasing temperatures. We tested whether the autumn and spring migration dates of eleven common frugivorous birds depended on the crop size of trees or ambient temperatures using 29 years of data in Finland. The increased crop sizes of trees delayed autumn migration dates; whereas, autumn temperature did not show a significant connection. We also observed a temporal trend towards later departure. Increasing temperature and crop sizes advanced spring arrival dates. Our results support the hypothesis that the timing of autumn migration in the frugivorous birds depends on the availability of food and is weakly connected with the variation in temperature. Importantly, crop size can have carry-over effects and affect the timing of spring arrival possibly because birds have overwintered closer to the breeding grounds after an abundant crop year.